2017
DOI: 10.5114/biolsport.2017.69817
|View full text |Cite
|
Sign up to set email alerts
|

Is the technical performance of young soccer players influenced by hormonal status, sexual maturity, anthropometric profile, and physical performance?

Abstract: The aim of this study was to examine the influence of hormonal status, anthropometric profile, sexual maturity level, and physical performance on the technical abilities of 40 young male soccer players during small-sided games (SSGs). Anthropometric profiling, saliva sampling, sexual maturity assessment (Tanner scale), and physical performance tests (Yo-Yo and vertical jumps) were conducted two weeks prior to the SSGs. Salivary testosterone was determined by the enzyme-linked immunosorbent assay method. Techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 24 publications
2
20
0
2
Order By: Relevance
“…A second objective of the present study was to analyze the relationships between playing time accrued, matches as starter, and the remaining anthropometric and maturation-related variables. Some studies have suggested relationships between anthropometry/body composition and maturation-related variables with technical performance ( Moreira et al, 2017 ), physical performance ( Philippaerts et al, 2006 ), and match-running performance ( Lovell et al, 2019 ). Indeed, considering the influence of anthropometry/body composition and maturity on the aforementioned measures, we hypothesized possible relationships with playing time accrued and matches as starters.…”
Section: Discussionmentioning
confidence: 99%
“…A second objective of the present study was to analyze the relationships between playing time accrued, matches as starter, and the remaining anthropometric and maturation-related variables. Some studies have suggested relationships between anthropometry/body composition and maturation-related variables with technical performance ( Moreira et al, 2017 ), physical performance ( Philippaerts et al, 2006 ), and match-running performance ( Lovell et al, 2019 ). Indeed, considering the influence of anthropometry/body composition and maturity on the aforementioned measures, we hypothesized possible relationships with playing time accrued and matches as starters.…”
Section: Discussionmentioning
confidence: 99%
“…These tests are usually carried out by women's football teams [17,[23][24][25][26][27], since they provide valid data to evaluate the anthropometry and physical condition of players. Therefore, all participants were familiar with the tests and performed them regularly.…”
Section: Temporalizationmentioning
confidence: 99%
“…The body mass index (BMI), which is an anthropometric indicator commonly used in studies with athlete populations [1,25,28,29], was calculated. The sum of six skinfolds (Σ6skinfolds: triceps, subscapular, supraspinal, abdominal, medial thigh, maximum calf), was used to estimate fat (%Fat) and muscle (%Muscle) percentage.…”
Section: Procedures 241 Anthropometrymentioning
confidence: 99%
“…32 quienes analizaron futbolistas juveniles de Bélgica y Moreira y cols. 33 que evaluaron a futbolistas profesionales de Brasil. Lo que refleja que el Yo-Yo test es un instrumento confiable para medir de manera indirecta la capacidad cardiorrespiratoria en futbolistas 34 .…”
Section: Discussionunclassified